Wrinkle-induced highly conductive channels in graphene on SiO2/Si substrates. Issue 22 (29th May 2020) - Ma, Rui-Song; Ma, Jiajun; Yan, Jiahao; Wu, Liangmei; Guo, Wei; Wang, Shuai; Huan, Qing; Bao, Lihong; Pantelides, Sokrates T.; Gao, Hong-Jun
Abstract : This work helps to pave the way toward practical applications with wrinkled graphene as electrodes in electrical devices. Abstract : A graphene wrinkle is a quasi-one-dimensional structure and can alter the intrinsic physical and chemical activity, modify the band structure and introduce transport anisotropy in graphene thin films. However, the quasi-one-dimensional electrical transport contribution of wrinkles to the whole graphene films compared to that of the two-dimensional flat graphene nearby has still been elusive. Here, we report measurements of relatively high conductivity in micrometer-wide graphene wrinkles on SiO2 /Si substrates using an ultrahigh vacuum (UHV) four-probe scanning tunneling microscope. Combining the experimental results with resistor network simulations, the wrinkle conductivity at the charge neutrality point shows a much higher conductivity up to ∼33.6 times compared to that of the flat monolayer region. The high conductivity can be attributed not only to the wrinkled multilayer structure but also to the large strain gradients located mainly in the boundary area. This method can also be extended to evaluate the electrical-transport properties of wrinkled structures in other two-dimensional materials.